Use of acceleration sensors in archery - Eckelt, M.; Mally, F.; Brunner, A. (Proceedings, 2020)
Archery is a quasi-static sport. Nevertheless, it requires maximum concentration, as well as precision from the archer. Previous research used combinations of several sensors, video analysis and electromyography to analyse the motion sequence and to identify parameters leading to a worse score. Therefore, the aim of this study is to verify if solely an acceleration sensor on the archer`s hand, without complex data processing, could be used to set up a feedback system. For testing, six participants with a three dimensional acceleration sensor on each hand shot indoors at a vertical triple target. The parameters analysed were the duration of the movement, the range of motion and the coefficient of variation. The results indicate that the analysis of the coefficient of variation shows no correlation with the score reached, whereas the analysis of the duration and the range of motion does.